Development and validation of students' achievement, ability to ask and inductive thinking instruments in the static fluid course. Issue 1 (March 2021) - Halim, A; Ayunda, D S; Susanna; Mustafa; Syukri, M; Irwandi
Abstract: The purpose of this article is to discuss the results of developing several test and non-test instruments to be used as a measurement of learning outcomes, questioning skills and students' inductive thinking skills. Development using the ADDIE model. Based on expert assessments and trials on a limited sample, 20 items were obtained for the learning outcomes instrument, 12 items for the non-test question ability and 10 items for the non-test instrument inductive thinking ability. The results of the analysis of data for the Learning Outcomes Test of Statis Fluid (LOTSF), the Questioning Ability Observation Sheet instrument (QAOS), and the Inductive Thinking Ability Observation Sheet (ITAOS) instrument obtained a validity of 0.6 and a reliability value of 0.75. Inference from this study to lecturers or teachers who teach Static Fluid concepts can follow the test development procedure offered in this article or use instruments produced from this study.